Motivation Measurement model to Learn Basic Buliding Construction and Survey Engineering using Confirmatory Factor Analysis - Iqrammah, Evany; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2019)
The purpose of this study was to produce an instrument of learning motivation in the subject of Basic Building Construction and Survey Engineering (DKBT) using factor analysis. Conceptually, the learning motivation instrument developed has two factors, specifically intrinsic and extrinsic. The subjects of the research were the 11th grade students of SMKN 3 Jombang second semester 2018/2019 totaling 62 people. Data were analyzed using SPSS 24, including instrument reliability indicators (Cronbach Alpha), Kaiser-Meyer-Olkin (KMO), percentage of construction variance, and item validity (loading factor). The results showed that the Cronbach Alpha value in the classification was higher than 0.70 that was 0.93, the KMO price was 0.681, the construction variance percentage was 68.39%, and the factor load was all items ≥0.3. Thus the measurement model is suitable for measuring the learning motivation of DKBT students in the Modeling Design and Building Information.